Gut Microbiota as a Trigger of Accelerated Directional Adaptive Evolution: Acquisition of Herbivory in the Context of Extracellular Vesicles, MicroRNAs and Inter-Kingdom Crosstalk - Romano, Marco (Frontiers in Microbiology, 2017)
According to a traditional view, the specific diet in vertebrates is one of the key factors structuring the composition of the gut microbiota. In this interpretation, the microbiota assumes a subordinate position, where the larger host shapes, through evolution and its fitness, the taxonomical composition of the hosted microbiota. The present contribution shows how the evolution of herbivory, framed within the new concept of holobiont, the possibility of inter-kingdom crosstalk and its epigenetic effects, could pave the way to a completely reversed interpretation: instead of being passively shaped, the microbiota can mold and shape the general host body structure to increase its fitness. Central elements to consider in this context are the inter-kingdom crosstalk, the possibility of transporting RNAs through nanovesicles in feces from parents to offspring, and the activation of epigenetic processes passed on vertically from generation to generation. The new hypothesis is that the gut microbiota could play a great role in the macroevolutionary dynamics of herbivorous vertebrates, causing directly through host-microbiota dialogue of epigenetic nature (i.e., methylation, histone acetylation, etc.), major changes in the organisms phenotype. The vertical exchange of the same microbial communities from parents to offspring, the interaction of these microbes with fairly uniform genotypes, and the socially restricted groups where these processes take place, could all explain the reasons why herbivory has appeared several time (and independently) during the evolution of vertebrates. The new interpretation could also represent a key factor in understanding the convergent evolution of analogous body structures in very distant lineages.